The Concept of Mafhum al-Nash in the Thought of Nashr Hamid Abu Zaid: A Comparative Analysis with the Literal Approach of Khawarij - Wathani, Muhammad Fadhil; Sholeh, Muhammad Badrus; Salamah, Ika Hilmiatus; Sulaiman, Sulaiman; Amin, Nasihun; Wibowo, Taufik Awan (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2025)
This study examines the relationship between the thought of Nashr Hamid Abu Zaid and the ideology of Khawarij, focusing on the analysis of the concept of "Mafhum al-Nashsh".  As a progressive Muslim thinker, Abu Zaid offers a critical approach to textual understanding in Islam that emphasizes the importance of context and dynamic interpretation. On the other hand, Khawarij is known for its literal and radical approach to religious texts.  By analyzing Abu Zaid's works, this article identifies the intersection and the fundamental differences between Abu Zaid's critical approach and the Khawarij's textual views.  This study examines Abu Zaid's response to the Khawarij ideology and assesses the implications of this relationship for contemporary Islamic understanding and efforts to counter religious extremism.  The research results are expected to make a significant contribution to understanding the dialectic between progressive and literal thought in Islamic discourse. Studi ini menyelidiki hubungan antara pemikiran Nashr Hamid Abu Zaid dan ideologi Khawarij, dengan penekanan pada analisis konsep "Mafhum al-Nashsh". Sebagai pemikir Muslim progresif, Abu Zaid menawarkan pendekatan kritis terhadap pemahaman tekstual dalam Islam yang menekankan pentingnya konteks dan interpretasi dinamis. Di sisi lain, Khawarij dikenal karena pendekatannya yang harfiah dan radikal terhadap teks-teks agama. Melalui analisis karya-karya Abu Zaid, artikel ini mengidentifikasi persimpangan serta perbedaan mendasar antara pendekatan kritis Abu Zaid dan pandangan tekstual Khawarij.  Studi ini tidak hanya mengungkapkan bagaimana Abu Zaid menanggapi ideologi Khawarij, tetapi juga mengevaluasi implikasi dari hubungan ini terhadap pemahaman Islam kontemporer dan upaya untuk melawan ekstremisme agama. Hasil penelitian diharapkan dapat memberikan kontribusi yang signifikan dalam memahami dialektika antara pemikiran progresif dan harfiah dalam wacana Islam.